A culturally-sensitive approach to sexual and reproductive health education: a critical review of a parenting sexuality book - Ellin, Mohammed Rasheedan; Abdul Hamid, Siti Hazariah; Mohd Arifin, Siti Roshaidai; Hasan, Haliza; Huriah, Titih; Othman, Sajaratulnisah; Mohd Zain, Norhasmah (Karya Ilham Publishing, 2025)
Sexual and Reproductive Health (SRH) education has become increasingly critical in contemporary society, with reports of child sexual and physical abuse appearing almost weekly in mainstream media. The current generation of parents, who were raised in environments where discussions about sexuality were relatively private and infrequent, now face the challenge of addressing these issues with their teenage children. Consequently, there is a pressing need to raise awareness and equip parents with the necessary skills for effective communication about SRH. This review examines the book "Berbual-bual dengan Anak tentang Seksualiti (BBDATS)" by Wan Nur Syakira Wan Musa, analyzing its content, purpose, and relevance. The book uniquely integrates Islamic perspectives, which is essential for addressing the needs of Malaysia's predominantly Muslim population. It ensures the content respects cultural and religious norms while promoting effective SRH education. The book features 18 engaging chapters, employing various techniques such as dialogue, highlights, Q&A sections, checklists, and step-by-step guides, making it relevant and accessible. By skillfully linking Islamic knowledge sources, such as the Quran and Hadith, with practical storytelling methods, the book helps readers connect fundamental life principles with the technical skills needed for effective communication. This review highlights the valuable insights provided by BBDATS, suggesting that benchmarking its best practices can enhance SRH education initiatives